Deoxyribonucleic Acid Base Composition of Some Members of the Micrococcaceae - Auletta, Angela E. (1966)
Auletta, Angela E. (Catholic University, Washington, D.C.), and E. R. Kennedy. Deoxyribonucleic acid base composition of some members of the Micrococcaceae. J. Bacteriol. 92:28–34. 1966.—Thirty-seven strains from the genera Micrococcus, Staphylococcus, Gaffkya, and Sarcina were examined for deoxyribonucleic acid base composition and biochemical activity. Organisms were tested for production of catalase, coagulase, deoxyribonuclease, oxidase, phosphatase, hydrogen sulfide, indole, and acetoin; nitrate reduction; gelatin, starch, and urea hydrolysis; citrate and ammonium phosphate utilization; NaCl tolerance; growth at 10 and 45 C, and growth in litmus milk. They were tested for production of acid from dextrose and mannitol under anaerobic conditions, and for aerobic production of acid from dextrose, mannitol, lactose, sucrose, raffinose, maltose, xylose, and glycerol. Organisms could be divided into two groups on the basis of guanine-cytosine (GC) content. Group I had an average GC content of 32%, and included all organisms which produced acid from dextrose. Group II had an average GC content of 62%, and included those organisms incapable of producing acid from dextrose under anaerobic conditions. Sarcina ureae had a GC content of 43%.